Challenges of Eco-Sustainability Campaign and Environmentalism in Nigeria: The Way Forward - Christian, Nche George (Mediterranean Journal of Social Sciences, 2012)
The effects of Climate change alongside its attendant environmental issues have become glaring anddevastating in Nigeria. Is it to talk about the incidence of flood that have cataclysmically wrecked severalstates in the Country, the massive loss of lives and property, or the increased York of poverty anddestitution that have befallen thousands of people as a result of climate change? Good enough, there hasbeen eco-sustainability campaigns and environmentalism in the country. These campaigns aim atstabilizing the earth’s eco systems while encouraging environmental sustainability. Beyond this challengealready posed by the phenomenon of climate change, this Paper seeks to discuss the external challengesmilitating against efficient eco-sustainability campaigns in the Country. The rueful lack of fund, facilities,adequate environmental Training and the menace of corruption, high insecurity, poverty and poorlyregulated population growth, have been found to be these challenges. The Paper however, recommendsconcerted efforts from both the government and other stakeholders, in order to successfully combat climatechange and its effects in the Country.